Effective Strategies for Heterologous Expression of Plant Heterotrimeric G-protein γ Subunits without Gβ Subunit Partners - Avsar, Bihter (Protein and Peptide Letters, 2022)
Background: In plants, heterotrimeric G-protein (Gγ) subunits are diverse, and they have structural plasticity to provide functional selectivity to the heterotrimer. Although the Gβ and Gγ subunits dimerize to function in the signaling pathway, the interaction mechanism of various Gγ subunits with the Gβ subunit partners is still elusive. Objective: To better understand the interaction mechanism, one approach is to separate the subunits for the re-assembly in vitro. Hence, developing a reliable method for achieving the efficient production and purification of these proteins has become necessary. Methods: In this study, Gγ1 and Gγ2 proteins from Oryza sativa and Arabidopsis thaliana were successfully identified, cloned, expressed in bacteria, and purified as recombinant proteins with the fusion tags. Highly expressed recombinant Gγ subunits in E. coli were digested by proteases, which were also produced in the presented study. Results: Preliminary structural characterization studies without the Gβ partners showed that Gγ1 proteins have disordered structures with coiled-coil, α-helix extensions, and loops, whereas the Gγ2 protein has a more dominant β-sheet and turns structure. Finally, computational analyses performed on Gγ genes have laid the foundation of new targets for biotechnological purposes. Conclusion: The proposed optimized expression and purification protocol can contribute to investigations on the Gβγ binding mechanism in plant G-protein signaling. The investigations on selective binding are critical to shed light on the role(s) of different plant Gγ subunit types in biological processes.
Keywords: RGG2